Keefektifan Model Problem Based Learning (PBL) Berbantu Media Video Interaktif untuk Meningkatkan Pemahaman Hasil Belajar IPAS di SDN Kutoharjo 01 Pati - Yudha Adzana; Siti Masfuah; Ika Ari Pratiwi (Mathematics Education Study Program, 2025)
The monotonous learning process and rarely using video media causes low student learning outcomes. This often happens considering the constraints of video media support tools. The purpose of this study is to measure the improvement of students' understanding of science using the Problem Based Learning (PBL) learning model assisted by Interactive Video Media for science subjects. This type of research uses quantitative research with a Pre-Experimental design approach with the type of One Group Pretest-posttest Design. This research was carried out in class V of SDN Kutoharjo 01 pati with a sample of 26 students. The data collection techniques in this study are observation, interviews and tests. The results of this study using the paired sample T-test obtained a value of 0.000 where (0.000<0.05) so that H0 was rejected where the learning outcomes of students after the application of the PPT-assisted video-based problem based learning model were better than before the use of the model. The increase in the average pretest results was 65.4 for the pretest and 78.3 for the average posttest score with a t-8.457 value and an average N-Gain value of 0.36 in the medium category. The video-based Problem Based Learning learning model assisted by PPT media is effective for improving student learning skills, so that it can be a solution for teachers to create more active, effective learning so that learning outcomes are good.